Genome-wide identification and functional analysis of Cellulose synthase gene superfamily in Fragaria vesca - Huang, Hexin; Zhao, Shuai; Chen, Junli; Li, Tianxiang; Guo, Ganggang; Xu, Ming; Liao, Sufeng; Wang, Ruoting; Lan, Jiayi; Su, Yangxin; Liao, Xiong (Frontiers in Plant Science, 2022)
The Cellulose synthase (CesA) and Cellulose synthase-like (Csl) gene superfamilies encode key enzymes involved in the synthesis of cellulose and hemicellulose, which are major components of plant cell walls, and play important roles in the regulation of fruit ripening. However, genome-wide identification and functional analysis of the CesA and Csl gene families in strawberry remain limited. In this study, eight CesA genes and 25 Csl genes were identified in the genome of diploid woodland strawberry (Fragaria vesca). The protein structures, evolutionary relationships, and cis-acting elements of the promoter for each gene were investigated. Transcriptome analysis and quantitative real-time PCR (qRT-PCR) results showed that the transcript levels of many FveCesA and FveCsl genes were significantly decreased during fruit ripening. Moreover, based on the transcriptome analysis, we found that the expression levels of many FveCesA/Csl genes were changed after nordihydroguaiaretic acid (NDGA) treatment. Transient overexpression of FveCesA4 in immature strawberry fruit increased fruit firmness and reduced fresh fruit weight, thereby delaying ripening. In contrast, transient expression of FveCesA4-RNAi resulted in the opposite phenotypes. These findings provide fundamental information on strawberry CesA and Csl genes and may contribute to the elucidation of the molecular mechanism by which FveCesA/Csl-mediated cell wall synthesis regulates fruit ripening. In addition, these results may be useful in strawberry breeding programs focused on the development of new cultivars with increased fruit shelf-life.